TINGKAT PEMAHAMAN PEMILIK RESTORAN DAN KONSUMENNYA TENTANG PAJAK RESTORAN - SETIAWANTO, RISKY (Jurnal Akuntansi AKUNESA, 2013)
Background research is due to happen by disappointment caused consumers still lack ofrestaurants that charge VAT, leading to misunderstanding. But local authorities in this citygovernment has since socialization must Surabaya 2011. This research aims to determine thelevel of understanding of restaurant owners and consumers will tax the restaurant. This researchis descriptive research analytical analyzed qualitatively using primary data. The Data obtainedthrough the questionnaire with the restaurant manager and ten customers. Based on the researchresults, then it can be inferred that the owner of the restaurant have a level of understandingabout the restaurant Tax of 70% (seventy percent), while the average level of understandingabout the consumers of Restaurant Tax 58,25% (fifty-eight comma twenty-five percent).Keywords: VAT, Restorant Tax, and Surabaya City Of Government.